2014
DOI: 10.2478/ffp-2014-0008
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Selected Traits of Ips Typographus (L.) (Col.: Scolytinae) Populations In Beskid Żwiecki (Western Carpathians, Poland) Region Affected By Bark Beetle Outbreak

Abstract: In 2010-2012, investigations on Ips typographus populations were carried out in Norway spruce stands recently affected by bark beetle outbreak in the Beskid Żywiecki Mts. in Poland. The aim of the study was to test the usefulness of several traits describing I. typographus populations for evaluation of their actual outbreak tendency. Infestation density, sex ratio, gallery length, progeny number and beetle length were used as the traits. Trait variability was analyzed in relation to infested tree mortality in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 17 publications
2
16
0
1
Order By: Relevance
“…(observed: 16.22 ± 6.95; expected 1: 16.24 ± 3.25) are close to those (expected 3: 17.29 ± 4.35) estimated using the equation from Beskidy Mts. (Grodzki et al 2014) and far lower than the values (expected 2: 27.97 ± 6.84) resulting from the equation proposed by Anderbrant (1990) (Fig. 5).…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…(observed: 16.22 ± 6.95; expected 1: 16.24 ± 3.25) are close to those (expected 3: 17.29 ± 4.35) estimated using the equation from Beskidy Mts. (Grodzki et al 2014) and far lower than the values (expected 2: 27.97 ± 6.84) resulting from the equation proposed by Anderbrant (1990) (Fig. 5).…”
Section: Discussionmentioning
confidence: 67%
“…When applying the simple regression model describing the relationship between the gallery length and number of progeny (see Fig. 3), as well as the other models based on the length of the maternal gallery proposed by Anderbrant (1990) and Grodzki et al (2014), both observed and expected average values from Kościeliska Valley were lower than the average number calculated using those models (Fig. 5).…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations